2019
DOI: 10.3390/ijerph16245140
|View full text |Cite
|
Sign up to set email alerts
|

Class Time Physical Activity Programs for Primary School Aged Children at Specialist Schools: A Systematic Mapping Review

Abstract: Children with disabilities tend to be less active than typically developing peers and may therefore miss important developmental benefits. Class time physical activity (PA) programs can provide additional PA to children and have shown to contribute to numerous benefits in mainstream classrooms. However, it is unclear whether class time PA opportunities are provided in specialist education settings. This review aimed to identify and map class time PA programs that have been implemented in specialist schools and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…A systematic mapping review of class time PA programs that have been implemented in specialist school settings revealed that only 11 out of 34 programs identified had been implemented through short (≤ 20 min) sessions and only seven of these were delivered by the classroom teacher [43]. Additionally, the review found that class time PA programs in specialist schools of any length had not been extensively evaluated, identifying only 23 programs involving a PA component that had been evaluated, four of which were implemented through brief sessions by the classroom teacher [43], representing an active break. Thus, further evaluation of PA break programs in specialist school classrooms is required to advance the limited evidence base and inform classroom practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic mapping review of class time PA programs that have been implemented in specialist school settings revealed that only 11 out of 34 programs identified had been implemented through short (≤ 20 min) sessions and only seven of these were delivered by the classroom teacher [43]. Additionally, the review found that class time PA programs in specialist schools of any length had not been extensively evaluated, identifying only 23 programs involving a PA component that had been evaluated, four of which were implemented through brief sessions by the classroom teacher [43], representing an active break. Thus, further evaluation of PA break programs in specialist school classrooms is required to advance the limited evidence base and inform classroom practice.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, to the best of our knowledge, only one study has specifically investigated the feasibility of an active break in specialist schools [38]. That is, while studies have evaluated outcomes associated with children participating in brief class time PA sessions in specialist classes (see [43]), Mazzoli and colleagues [38] were the first to conduct a feasibility study of an active break in a specialist school. The active break consisted of a cognitively challenging motor task, whose feasibility seems lower in specialist compared to mainstream schools, but may increase if motor tasks are tailored to children's specific needs [38].…”
Section: Introductionmentioning
confidence: 99%
“…Children with developmental disabilities are more likely to experience difficulties with physical activity (Emonson et al., 2019). They may have more challenges because of physical limitations, lack of accessible environments, and/or lack of resources (CDC, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…Children with disabilities also have been found to reach motor milestones later than same‐aged peers (CDC, 2021b; Hogan et al., 2000), including control of movement, motor sequencing, and concentration (Jeoung, 2018). Children with developmental disabilities have been found to have lower motor performance (e.g., dexterity, balance, and ball skills) than typically developing same‐aged peers (Vuijik et al., 2010), experience decreased levels of exercise compared to peers (CDC, 2021a; Thomas et al., 2016), and are unlikely to participate in moderate to rigorous physical activity (Emonson et al., 2019). Because 20% of children with disabilities are considered obese, the CDC (2019a) recommended increasing physical activity for children with disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…They require adaptations that increase with the severity of their motor impairment and with the presence of co-morbidities. The amount of physical activity practised by these children, who lead a much more sedentary lifestyle than other children, is significantly lower than the usual recommendations and time spent exercising for children without disabilities [ 2 ]. Previous studies [ 1 , 3 , 4 ] have mainly explored the limitations and facilitators of accessing physical activities for children with a physical disability.…”
Section: Introductionmentioning
confidence: 99%